Daily activities of teenagers with autism at home: a case report study - Jiu, Cau Kim; Gusmiah, Tisa; Erwhani, Indri; Febriyanti, Indriani (International Journal Of Community Medicine And Public Health, 2020)
Parents have an important role in supervising and directing their autistic teenagers while carrying out daily routines at home so they can become independent teens. The purpose of this case study is to provide an overview of how teenagers with autism carry out their daily activities and what their daily activities are at home. Data collection methods used in this study were in-depth interviews and observations. The results of this study indicate that teenagers with autism are involved by parent in carrying out daily activities at home such as folding clothes, cleaning the kitchen floor, and washing rice and vegetables while at the same time parent accompany, supervise and guide her daughter. Very important for mother to teaches and trains her autistic teenager in daily living activities at home to be independent.